2014
DOI: 10.1186/1999-3110-55-28
|View full text |Cite
|
Sign up to set email alerts
|

From leaf and branch into a flower: Magnolia tells the story

Abstract: BackgroundIn the classical doctrines, Magnolia was frequently considered the archetype among flowering plants, and its conduplicate carpel with marginal placentation was assumed to be derived from a leaf-like organ bearing ovules along its margins. Although the robustness of this concept has been seriously questioned by advances in botanical research, especially the emergence of Magnolia deeper in the angiosperm tree of life in molecular systematics, it remains the most-taught interpretation for the origin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 81 publications
(168 reference statements)
1
22
0
Order By: Relevance
“…This inconformity between traditional opinions and the present result is not confined to D. chinensis . Numerous taxa of angiosperms have been reported to support amphicribral vascular bundles in placenta, including Papaveraceae (Kapoor, 1973 , 1995 ), Leguminosae (Lersten and Don, 1966 ), Winteraceae (Tucker, 1975 ), Solanaceae (Dave et al, 1981 ; Wang et al, 2015 ), Gesneriaceae (Wang and Pan, 1998 ), Buxaceae (Von Balthazar and Endress, 2002 ), Annonaceae (Endress and Armstrong, 2011 ), Actinidiaceae (Guo et al, 2013 ), and Magnoliaceae (Liu et al, 2014 ; Wang et al, 2015 ), etc. These taxa cover the whole scope of angiosperms from the basal clade magnoliids to the terminal eudicot lineage in the phylogenetic tree (Angiosperm Phylogeny Group, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inconformity between traditional opinions and the present result is not confined to D. chinensis . Numerous taxa of angiosperms have been reported to support amphicribral vascular bundles in placenta, including Papaveraceae (Kapoor, 1973 , 1995 ), Leguminosae (Lersten and Don, 1966 ), Winteraceae (Tucker, 1975 ), Solanaceae (Dave et al, 1981 ; Wang et al, 2015 ), Gesneriaceae (Wang and Pan, 1998 ), Buxaceae (Von Balthazar and Endress, 2002 ), Annonaceae (Endress and Armstrong, 2011 ), Actinidiaceae (Guo et al, 2013 ), and Magnoliaceae (Liu et al, 2014 ; Wang et al, 2015 ), etc. These taxa cover the whole scope of angiosperms from the basal clade magnoliids to the terminal eudicot lineage in the phylogenetic tree (Angiosperm Phylogeny Group, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the flowers of Magnolia , the carpel with marginal placenta is composed of two mutually independent primordia (corresponding to the ovary wall and axilla placenta). The ovary wall and placenta respectively have their own independent vascular bundles, and vascular bundles in them are totally different as showed by the amphicribral vascular bundle in the placenta and the collateral ones in the ovary wall (Liu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…are widely distributed shrubs and trees that produce beautiful flowers in the spring. The Magnoliaceae have long been considered an ancient angiosperm family and much of the current research on members of this family focuses on their systematic evolution [ 19 , 20 ]. The studies of Magnoliaceae flower bud differentiation mostly involve morphological observation [ 21 ], leaving the molecular mechanisms underpinning their flower development largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Their ornamental characteristic has been noted because of their large flower and fragrant aroma. In recent years, study of the reproductive organs of Magnolias more commonly focuses on the origin and systematic evolution of flowers [19,20], as well as the physiological and biochemical regulation mechanism, and so on [21,22]. It has been demonstrated that AP3 (APETALA 3) homologues, AGL (AGAMOUS-LIKE) genes, and other transcription factors play an important role in regulating flower bud differentiation and the development in Magnolia wufengensis [23,24] and Magnolia sinostellata [25].…”
mentioning
confidence: 99%